PENGARUH TATA RUANG KANTOR DAN EFISIENSI KINERJA PEGAWAI TERHADAP MUTU PELAYANAN DI BALAI BESAR PENGEMBANGAN PENJAMINAN MUTU PENDIDIKAN VOKASI (BBPPMPV) BISNIS DAN PARIWISATA, SAWANGAN-DEPOK - Waluyo Waluyo; Harjoyo Harjoyo; Siti Zubaidah (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
The purpose of this study is to determine the effect of office layout on service quality and efficiency of employee performance on service quality and to determine the effect of office layout and employee performance efficiency simultaneously on service quality. This study uses quantitative methods to determine the relationship between variables in a population. The research sample was 67 people from a total population of 204 people. Sampling was carried out using a stratified random sampling technique based on the demographics of the respondents. The demographics of the respondents in this study included gender, age, years of service, and education level. These demographic factors are seen as influencing the quality of service which is the topic of this research. The results showed that the Fcount was 217.416 with a significance of 0.000. Testing by comparing sig = 0.000 < a = 0.05, as well as testing by comparing the calculated F value = 217.416 > Ftable = 3.140. Based on the test results, it can be concluded that together there is a significant influence between Office Layout and Employee Performance Efficiency on Service Quality.